PHOTOPHYSICAL PROPERTIES OF PHENYLAZOQUINOLIN-8-OL DYES: CORRELATION OF EXPERIMENTAL AND THEORETICAL DATA - Olaleye, Sefiu Olalekan; Adegboye, Toluwani Samuel; Adegoke, Olajire Aremu (Department of Chemistry Faculty of Science and Technology UIN Walisongo, 2025)
Azo compounds are well-known as coloring agents in the textile and leather industries. Hence, continuous efforts are being made to determine the properties of these colored compounds. In this study, the solvatochromic behaviors of three phenylazoquinolin-8-ol dyes (HQ-01 to HQ-03) were investigated in solvents of varying polarities and in buffer solutions, with an emphasis on correlating experimental and theoretical data. The compounds were synthesized via diazotization and diazocoupling reactions and characterized by UV-Vis, FTIR, and 1H NMR spectroscopy. Their electronic absorption spectra were studied using UV-visible spectroscopy in solvents of different polarities and in buffer solutions. Bathochromic shifts were observed with increasing solvent polarity and basicity. The chemistry and electronic character of the solvents, along with the chemical nature and position of the substituents, were found to be responsible for the observed solvatochromic properties. Theoretical data obtained from density functional theory (DFT) calculations revealed that the dyes possessed low energy gaps, particularly HQ-02, which accounted for the experimental red shifts observed in the UV spectra. Therefore, the synthesized azo compounds may serve as promising solvatochromic probes, colorimetric chemosensors, medicinal agents, or analytical reagents.